8 - Book Reviews: D. Wadada Nabudere, Imperialism and Revolution in Uganda (Tanzania Publishing House and Onyx Press) 1981 - London and Dar Es Salaam- 376 pages. - Campbell, Horace G. (Africa Development, 1981)
Horace CAMPELL, University of Dar-Es-Salaam.